Penyelenggaraan Intelijen Negara dalam Perspektif Hak Asasi Manusia - Monika Suhayati (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2010)
The intelligence body is the foremost line in national security system by conducting early detection and early warning system in preventing and overcoming any threat to national security. The confidential character of the intelligence body equipped with special authority has made possible it becomes a subject of human right violation. However, the acknowledgement and protection of the human right have been regulated in or constitution and the human right number 39 yaer 1999. This essay attemps to examine the complexion problems between the implementation of intelligence function to ensure the national security and the necessity of human right’s protection. In solving the problem, it is important to have the national intelligence law. The law must regulate the consideration of human right’s protection in the implementation of intelligence task and authority; in its profesional etic code and sworn; penalty sanction given in the event any violation; and the multilayered oversight to intelligence bodies.